Knowledge and Socioeconomic Status as The Factors of Pre-hospital Delay in Patients with Acute Coronary Syndrome - Yustina Ni Putu Yusniawati; Yuyun Yueniwati; Dewi Kartikawatiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
Acute Coronary Syndrome (ACS) is a cardiac emergency condition that requires fast and precise action while a pre-hospital delay in a patient to come to the ED is still common. This pre-hospital delay is related to the socioeconomic and knowledge factor. The purpose of this study is to determine the relationship of socioeconomic and knowledge with the pre-hospital delay of ACS patients to come to Integrated Heart Service in Emergency Department of Sanglah General Hospital, Denpasar. This research is a quantitative research with cross-sectional design and purposive sampling as data collection technique with 292 patients. The results showed that 55.8% of patients have low socioeconomic status and there are 71.6% of patients who do not know ACS. The pre-hospital delay, in this case, is associated with low socioeconomic status and knowledge of ACS so that health workers need to provide counseling to patients and families about ACS signs and symptoms, healthy lifestyles, and the importance of coming to theemergency department when signs of ACS are felt.